The effect of Strategic Human Resource Management Research in Higher Education Institution - Otto Berman Sihite; Martinus Tukiran (INTERNATIONAL JOURNAL OF SOCIAL, POLICY AND LAW, 2020)
In order to study what is a concern in order to enhance human resources, different forms of research have been performed. In addition to research undertaken by non-profit corporations and profit-oriented organizations. For this reason, this research is also often carried out by universities or higher education as a form of obligation in order to enhance awareness through innovation. This is due to a community phenomenon, especially industries engaged in services or hospitality, that needs to be improved. In general, all research carried out always results in the creation of human resources to make employees feel an attachment to always having a feeling of belonging to a corporation or company and wanting fulfillment in the organization through the different performances they perform. These findings have been extracted from two forms of methods that can be performed both qualitatively and quantitatively.